Adsorption of 4,4-Dithiodipyridine Axially Coordinated to Iron(Ii) Phthalocyanine on Au(111) as a New Strategy for Oxygen Reduction Electrocatalysis - Tasca-Gottardo, F; Tasca-Gottardo, F (WILEY-V C H VERLAG GMBH, 2018)
The coordination of PySSPy to FePc was monitored by UV/Vis spectroscopy while the adsobed FePc, anchored by PyS-Au(111), was examined by insitu STM in 0.1M HClO4 and X-ray photoelectron spectroscopy (XPS). Rotating-disc-electrode (RDE) and linear-sweep-voltammetry (LSV) studies on the resulting FePc-modified Au(111) electrodes in an oxygen-saturated 0.1M NaOH electrolyte exhibit excellent electrocatalytic properties for the oxygen reduction reaction (ORR), with a smaller overpotential than that observed for Au(111) with FePc deposited by direct adsorption from a benzene solution.